Options for adapting to climate change in livestock-dominated farming systems in the greater horn of Africa - Notenbaert, An Maria Omer; Mude, Andrew G.; Steeg, Jeannette van de; Kinyangi, James (2010)
The greater horn of Africa is one of the least developed regions in Africa. Livestock are an important economic resource and an essential asset for poor farmers in this region. Climate variability, population growth, low economic development, limited market integration, and low fertilizer use, amongst others put serious pressure on livestock production. The sustainability of the livestock production in the rangelands and the integrated crop-livestock systems is further jeopardised by climate change. The uncertainties associated with climate change impacts call for interventions that empower communities to effectively cope with current climatic variability and to adapt to unexpected future consequences. Risk management and climate-robust development both appear to be promising approaches. Index- based livestock insurance, for example, offers innovative opportunities for protecting farmers’ assets, while diversification in the arid- and semi-arid regions might turn into economically viable livelihood strategies. These adaptation options will only be adopted if the right systems of incentives and policies are put in place.